Microfacies Analysis and Depositional Model for the Black River -Trenton Carbonates (Ordovician) of Southern Ontario, Canada - El Gadi, Muftah (AlQalam Journal of Medical and Applied Sciences, 2024)
This study documents the detailed microfacies depositional environment of the Ordovician Black River and Trenton limestone Groups in Lake Simcoe area of southern Ontario, resting unconformably on Precambrian basement. Local Precambrian ’highs’ complicate the overall facies pattern and lithofacies patterns define local shoal, intershoal and basinal environments. Detailed microfacies and facies analysis in large quarries in the Lake Simcoe area are used to infer various carbonate environments by comparison with analogous modern and ancient ramps. Fifteen microfacies are grouped into six microfacies associations based on composition, grain size and texture. Relative energy levels, and depositional environments for these are then inferred. These environments resemble the Recent Arabian Shelf of the Persian Gulf for the Black River Group, and the Recent West Florida Shelf for the Trenton, though other Recent ramps like South Australia are also comparable. The vertical arrangement of faciein the Lake Simcoe area forms repetitive cycles, which can then be traced laterally into adjacent areas, complicated by the effects of sea-floor topography and possibly by synsedimentary faulting. هذه الدراسة توتق البيئة الترسيبية الدقيقة التفصيلية لنهر ألاوردوفيشي الأسود ومجموعات الحجر الجيري ترينتون في منطقة بحيرة سيمكو في جنوب أونتاريو، والتي تقع بشكل غير متوافق علي قبو ما قبل الكمبري. الارتفاعات المحلية في عصر ما قبل الكمبري عقدت نمط السحنات العام وأنماط الصخور الحجرية التي تحدد البيئات الضحلة المحلية، والبيئات بين الضحلة والحوضية. يتم استخدام تحاليل مفصلة للسحنات الدقيقة والسحنات في المحاجر الكبيرة في منطقة بحيرة سيمكو لاستنتاج بيئات الكربونات المختلفة بالمقارنة مع المنحدرات الحديثة والقديمة المماثلة. تم دمج خمسة عشر سحنة دقيقة في ستة مجموعات من السحنات الدقيقة بناء على التركيب وحجم الحبيبات والملمس. ثم الاستدلال على مستويات الطاقة النسبية والبيئات الترسيبية لها. تشبه هذه البيئات الجرف العربي الحديث للخليج الفارسي لمجموعة النهر الأسود ، وجرف غرب فلوريدا لترينتون ، على الرغم من أن المنحدرات الحديثة الأخرى مثل جنوب أستراليا قابلة للمقارنة أيضا. يشكل الترتيب الرأسي للسحنات في منطقة بحيرة سيمكو دورات متكررة يمكن بعد ذلك تتبعها أفقيا في المناطق المجاورة، عقدة بسبب تأثيرات تضاريس قاع البحر وربما بسبب الصدوع الرسوبية